UTERINE FIBROIDS: SYMPTOMS SEVERITY AND ITS IMPACT ON HEALTH-RELATED QUALITY OF LIFE AMONG WOMEN IN REPRODUCTIVE AGE GROUP IN NORTH KERALA - ANTONY V, ABHILASH; T, HEERA SHENOY; SHIVAKUMAR,; VK, CHELLAMMA; HASHIM, HIBA (Asian Journal of Pharmaceutical and Clinical Research, 2022)
Objectives: This study was conducted to determine the effect of uterine fibroids (UFs) and their symptoms severity and its impact on health-related quality of life (QoL) among women in reproductive age group reporting to a teaching medical institution in the state of Kerala. Methods: The questionnaire QoL-life quality of patients with symptomatic UF was used to assess their QoL in 104 women attending outpatient department at KMCT Medical College from March 2021 to August 2021. Results: Mean age was 45.86. About 34.62% of cases were in Obesity I category; followed by 13.46% of Obesity II. About 33.65% had UF with corporeal location; 44.23% in cervical and 22.12% had isthmic fibroids. About 32.69% showed presence of sub-serous; 42.67% had intramural and 24.04% had submucosal fibroid. HMB followed by abdominal pain and bladder dysfunction was the presenting features. Conclusion: There was a strong negative correlation between symptoms and the UF QoL. This shows that with the increase in symptoms; the QoL was reduced in all the overall aspects. Hence, it was concluded that UF has a profound negative impact on the overall QoL in reproductive age women.